Evaluating the potential of solenoid motion system for electric vehicle -challenging the conventional usage of electric motor - Bahrin S.Z.A.S.K.; Razali N.M.M.; Jalal T.S.; Anisa U.; Amirulddin U. (2023)
Designing an electric vehicle (EV) using electric motor as its prime mover is very common. However, incorporating the electric motor to the overall EV design is relatively complex. The latest layout design of an EV requires a complex controller to govern the whole system especially the electric motors. Due to this complexity, the authors have developed an alternative electromagnetic prime mover for EV to replace the existing electric motor. This new prime mover is designed based on the solenoid concept and the internal combustion engine (ICE) working mechanisms. In this paper, the authors are introducing a new electromagnetic prime mover known as Solenoid Powered Engine (SPE). The paper describes the SPE underlying concepts, its comparison with electric motor in EV design, overall system layout, operations and characteristics. 2008 IEEE.